Respuesta :

Answer:

Option B:

[tex](x-4)^2+(y-1)^2 = 4[/tex]

Step-by-step explanation:

Given

Centre = (h,k) = (4,1)

Radius = r = 2

The standard equation of circle is:

[tex](x-h)^2+(y-k)^2=r^2[/tex]

Putting the values of h,k and r

[tex](x-4)^2+(y-1)^2 = (2)^2\\(x-4)^2+(y-1)^2 = 4[/tex]

Hence, the correct option is option B

[tex](x-4)^2+(y-1)^2 = 4[/tex]

Answer:

B

Step-by-step explanation:

The equation of a circle in standard form is

(x - h)² + (y - k)² = r²

where (h, k) are the coordinates of the centre and r is the radius

here (h, k ) = (4, 1) and r = 2, hence

(x - 4)² + (y - 1)² = 4 → B

ACCESS MORE